Urban agricultural activities, a food system resilience strategy during COVID-19 in Haiti - B. Paul (Пищевые системы)
The COVID-19 crisis is impacting the reconfiguration of food systems at different scales. In poor countries where food insecurity had already been a major problem, the urban population under the lockdown often had to cope alone with shortages of food and access to it. In the poorest country in the Americas, the urban population adapted the food system by intensifying the practice of urban agricultural activities. In this exploratory research, using a sample including urban dwellers that were engaged in urban agriculture and those who were not, we investigated the following question: Did urban agriculture linked to COVID-19 represent an appropriate and innovative strategy for the urban food system resilience? Our results confirm that the Haitian urban population used urban agriculture as an innovative and appropriate food resilience strategy. They produced varieties chosen for their very rapid production character and were able to cope successfully with the crisis, and also have lessons to share with other actors and countries.